ANALISIS PENGELOLAAN DANA ZAKAT UNTUK PENINGKATAN EKONOMI MASYARAKAT - Ahmad Hamid; Wiwin Sultraeni; Fitriadi Fitriadi; Rani Murwani; Puji Rahmah; Asnia Minarti; Surianti Surianti (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2023)
Zakat is one of the Pillars of Islam that is obligatory for a Muslim who has reached Nishab (Limitation), as explained in the Al-Qur'an Surat At-Taubah Verse 103. One of the objectives of zakat management is to increase public awareness in performing zakat worship. When zakat funds are collected, they can be used to improve the community's economy, especially for mustahiq (people who are entitled to receive zakat). The Kendari City National Amil Zakat Agency (BAZNAS) has a vision that the Islamic community of Kendari City is aware and obedient in paying zakat. the purpose of this study was to determine the management of zakat funds to improve the economy of the Kendari city community. The results of this study indicate that Zakat Management at the Kendari City National Amil Zakat Agency (BAZNAS). Only provide funds to help improve the community's economy through distribution, especially to the poor. However, some mustahiq have taken the initiative to utilize their zakat funds for business activities and income. The limited zakat funds received so that mustahiq who take the initiative to utilize zakat funds for business activities find it difficult to run their business in a sustainable manner